The percentage of contribution on some physical measurement of throw blind youth judo player skills - Farhan, Ahmed (Journal of Physical Education, 2019)
The purpose of the study is learn some physical measurement contribute in throw skills to blind youth judo players and knowing relationship between them. Researcher use the descriptive approach survey manner and study the relation connectivity. The research sample was 17 youth players (17-19) year from Baghdad clubs and after presages the conclusion was finding relationship between physical measurement and skills and they are effective in throw skills